Synergistic effect of pyrvinium pamoate and posaconazole against Cryptococcus neoformans in vitro and in vivo - Li, Yali; Li, Sheng; Chen, Min; Xiao, Jialing; Fang, Hong (Frontiers in Cellular and Infection Microbiology, 2022)
Background Cryptococcosis is a global invasive mycosis with high rates of morbidity and mortality, especially in AIDS patients. Its treatment remains challenging because of the limited antifungals and their unavoidable toxicity, and as such more efforts need to focus on the development of novel effective drugs. Previous studies have indicated that pyrvinium pamoate (PP) has individual and synergistic fungistatic effect. In this study, the effects of PP alone and in combination with azoles [fluconazole (FLU), itraconazole (ITR), voriconazole (VOR), posaconazole (POS)] or amphotericin B (AmB) were evaluated against Cryptococcus neoformans both in vitro and in vivo. Methods A total of 20 C. neoformans strains collected from cryptococcal pneumonia and cryptococcal meningitis were studied. The effects of PP alone, PP-azoles and PP-AmB interactions against C. neoformans were evaluated via the microdilution chequerboard technique, adapted from broth microdilution method according to the CLSI M27-A4. The in vivo antifungal activity of PP alone and in combination with azoles and AmB against C. neoformans infections was evaluated by Galleria mellonella survival assay. Results The in vitro results revealed that PP individually was ineffective against C. neoformans (MIC>16 μg/ml). Nevertheless, the synergistic effects of PP with ITR, VOR, POS, FLU or AmB was observed in 13 (65.0%, FICI 0.188–0.365), 3 (15.0%, FICI 0.245-0.301), 19 (95.0%, FICI 0.188-0.375), 7 (35.0%, FICI 0.188-0.375), and 12(60.0%, FICI 0.281-0.375) strains of C. neoformans, respectively. There was no antagonism. The survival rates of larvae treated with PP (3.33%) showed almost no antifungal effective, but the larvae survival rates improved when PP combined with AmB (35% vs. 23.33%), FLU (40% vs. 25%), ITR (48.33% vs. 33.33%), VOR (48.33% vs. 53.33%) and POS (56.67% vs. 36.67%) comparison with AmB or azoles alone, and statistical significance was observed when PP combined with POS versus POS alone (P = 0.04). Conclusions In summary, the preliminary results indicated the potential of PP in reduction the MICs of azoles and AmB, also itself against C. neoformans; the combination of PP with AMB, FLU, ITR, VOR and POS improve the survival rates of C. neoformans infection larvae, compared with they are alone. The in vitro and in vivo data show that PP could enhance the activity of POS against C. neoformans. This study contributes with data of PP in combination with classical drugs of choice for cryptococcosis treatment.